Attitudes toward and usage of face masks or face coverings among certified athletic trainers during the covid-19 pandemic - Andrew, S. C.; Brandon, W.; David, M.; Warner, L.; Diana, G.; Laurel, T.; Christina, T.; Julie, G. (Research & Investigations in Sports Medicine, 2020)
Following the widespread transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the majority of colleges and high schools canceled all face-to-face courses and athletic activities. As institutions allowed for athletes to return to campus, many institutions and government entities enacted requirements for the use of face masks or face coverings in public. Current research is being conducted to evaluate the epidemiology, recognition, treatment, and prevention of coronavirus disease 2019 (COVID-19), the disease associated with SARS-CoV-2. At the time of this study, there is no published research on attitudes toward and usage of face masks or face coverings among certified athletic trainers during the COVID-19 pandemic. The purpose of this study was to describe these attitudes toward face masks or face coverings and usage in this context. A total of 265 certified athletic trainers participated in this study (age= 42 ± 12, years of certified experience = 18 ± 11). An electronic survey was sent to these participants via email to collect demographic information and assess their attitudes toward and usage of face masks or face coverings. Data was downloaded and analyzed using a commercially available statistics package. The overwhelming majority of certified athletic trainers in this study, agreed on some level, the use of face masks to mitigate the transmission of SARS-CoV2 was strongly supported by the available evidence (Strongly Agree = 55.8%, Agree = 26.4%, Somewhat Agree = 9.4%). Most athletic trainers also reported that their institutions currently had mandates in place requiring face masks during patient encounters and coworker interactions (Patient Encounters = 66.4%, Coworker Interactions = 57.4%). Most athletic trainers reported wearing face masks the majority of the time when entering public spaces outside of work. Athletic trainers cited influence of their personal use of face masks, was for personal health, health of those in their household, and attempting to be a role model of best practices for public health. The findings of this study suggest a majority of athletic trainers are wearing face masks or face coverings, even when not actively involved in patient care or other aspects of their jobs.